PENGARUH STRUKTUR MODAL, ALOKASI PAJAK, DAN UKURAN PERUSAHAAN TERHADAP EARNING RESPONSE COEFFICIENT (ERC) PADA INDUSTRI PERKEBUNAN - Oktaviani, Yolanda; Wirianata, Henny (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to analyze the influence of Capital Structure, Tax Allocation, and Company Size on the Earning Response Coefficient (ERC). The population used in this research is plantation sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018 - 2022 period. The sample in this study was determined using a purposive sampling method and came from 22 plantation companies, so the total The sample amounted to 110 samples. Data processing was carried out using the multiple linear regression method with the help of SPSS software version 20. The results of the study showed that partially the Capital Structure variable had a negative and significant effect on the ERC, the Tax Allocation variable had a positive and significant effect on the ERC and the Company Size variable has a negative and significant effect on the ERC. The research results also show that Capital Structure, Tax Allocation, and Company Size simultaneously have a significant effect on the ERC